Assessment of immunization data quality of routine reports in Ho municipality of Volta region, Ghana - Sorengmen Amos Ziema; Livingstone Asem (BMC, 2020)
Abstract Background Immunization has been an important public health intervention for preventing and reducing child morbidity and mortality over the years and coverage has increased in the past decades. However, the validity of the data from immunization coverages is usually disputed. Immunization data from health facilities show poor concordance between tallied registers and monthly reports as they are reported to higher levels of the health system. The study assessed the quality of data from routine immunization of some health facilities in the Ho central municipality in the Volta region of Ghana. Methods A descriptive cross-sectional study was used to review routine immunization data in tallied registers and reports submitted to the Municipal Health Directorate (MHD) from January to December, 2015. Simple random sampling was used to select three health facilities in Ho central municipality. The World Health Organization (WHO) Data Quality Self-assessment (DQS) tool was the main instrument used to present and analyze data for accuracy and discrepancy level between the tallied registers and reports. A template was created in Microsoft excel which automatically presented accuracy and discrepancy levels when data was entered. Ethical approval for the study was obtained from Ghana Health Service Ethics Review Committee. Results The result showed discrepancies between recounted tallies at the facilities and reports submitted to the MHD. Accuracy ratios of 102, 64 and 94% for Bacillus Calmette Guerin (BCG), Pentavalent (Penta) vaccine dose 3 and Measles 2 respectively indicating underreporting for BCG and over reporting for the rest were obtained. There was 460 over reported data to the municipal level representing accuracy ratio of 80% and discrepancy level of 20%. Conclusions Immunization data was characterized by underreporting and overreporting, hence not accurate and lacked quality. Immunization data quality should be a priority among health staff at health facilities.